2009
DOI: 10.1007/s10753-009-9165-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ERK Activation in Human Mast Cells Stimulated by Contact with T Cells

Abstract: Close physical proximity between mast cells and T cells has been demonstrated in several human conditions. We have identified and characterized a novel mast cell activation pathway initiated by contact with T cells, and showed that this pathway is associated with cytokine release. It has been shown recently that Ras is activated in this pathway. Thus, in the present study we further explore the downstream events associated with Ras activation and cytokine release in human mast cells stimulated by contact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…We recently showed that direct contact of human mast cells with T lymphocyte membranes resulted in the phosphorylation of the MAPK family (15,16). The MAPKs are known to play an important role in mediator release in human mast cells after IgEcross-linking or on activation by inducers, such as SCF and TNF-a (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that direct contact of human mast cells with T lymphocyte membranes resulted in the phosphorylation of the MAPK family (15,16). The MAPKs are known to play an important role in mediator release in human mast cells after IgEcross-linking or on activation by inducers, such as SCF and TNF-a (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown recently that stimulation of human mast cells by contact with activated T cells is associated with Ras activation and phosphorylation of the mitogen-activated MAPKs ERK (15,16). Therefore, we investigated whether microparticles derived from activated T cells were also able to induce ERK activation.…”
Section: T Cell-derived Microparticles Induce Erk Phosphorylation In mentioning
confidence: 97%
“…We have previously shown that stimulation of MC by T*m leads to degranulation and release of certain cytokines [1,2,3], and is associated with the phosphorylation of ERK and p38 [5]. The PKD family has been implicated in diverse cellular functions [7].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that heterotypic adhesion of MC to activated but not resting T cells induces MC degranulation and cytokine production in a pathway associated with the activation of Ras and the MAPK signaling pathway [1,2,3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation